Research on the influencing factors of DT of SMEs from TOE perspective - Zhang Yujie; Sidah Bt Idris; Jaratin Bin Lily (Global Business & Finance Review (GBFR), 2024)
Purpose: This paper is to examine how the DT of SMEs is affected and driven, and provide theoretical and practical implications for the DT of SMEs. Design/methodology/approach: Starting from the TOE framework, combined with the resource-based view and contingency theory, this study identifies the antecedents that affect the DT of SMEs from the three dimensions of technology, organization, and environment. Under the framework of TOE, digital technology infrastructure, employee skills, management support and environment uncertainty will be fully discussed. With the data from 221 SMEs from China analyzed by the fs_QCA 3.0, the driving paths for high DT are divided into different conditions configurations. Findings: The DT of SMEs is not the result of a single factor driven, but rather the result of the synergistic effect of the enterprise. There are multiple resource allocation configurations that drive the DT of SMEs, indicating the complexity and synergy of the factors affecting the DT of SMEs, which can prove the DT of SMEs has the characteristic of "multiple concurrency". Research limitations/implications: DT is a very complex phenomenon, and there are many factors that affect the DT of SMEs. Based on the TOE framework, this paper selects four factors, and many possible factors are not included in the model. Besides, for QCA, a case-based research method with a quantitative approach, structured questionnaire surveys often result in a lack of detailed understanding of the research subjects and the inability to delve into all case enterprises. Originality/value: The findings will enrich the research in the DT field, and deepen the rational understanding of the complex interaction nature of multiple factors behind the successful DT of SMEs and provide path guidance for SMEs to realize DT. The research conclusions of this study provide valuable insights for SMEs to promote DT by combining possible antecedent configurations.
Keywords: 650; Small and medium-sized enterprises (SMEs); Digital transformation (DT); Qualitative comparative analysis; Technology-organization-environment (TOE); Configuration factors; fsQCA